Brief Report: Case Comparison of Therapy With the Histone Deacetylase Inhibitor Vorinostat in a Neonatal Calf Model of Pulmonary Hypertension - Applegate, Tanya J.; Krafsur, Greta M.; Boon, June A.; Zhang, Hui; Li, Min; Holt, Timothy N.; Ambler, S. Kelly; Abrams, Benjamin A.; Gustafson, Daniel L.; Bartels, Karsten; Garry, Franklyn B.; Stenmark, Kurt R.; et al. (Frontiers in Physiology, 2021)
Pulmonary hypertension (PH) is an incurable condition in humans; driven by pulmonary vascular remodeling partially mediated by epigenetic mechanisms; and leading to right ventricular hypertrophy, failure, and death. We hypothesized that targeting chromatin-modifying histone deacetylases may provide benefit. In this Brief Report we describe case comparison studies using the histone deacetylase inhibitor vorinostat (suberanilohydroxamic acid, 5 mg/kg/day for the first 5 study days) in an established model of severe neonatal bovine PH induced by 14 days of environmental hypoxia. Echocardiography, hemodynamic and pharmacokinetic data were obtained in hypoxia-exposed (one each, vorinostat-treated versus untreated) and normoxic vorinostat-treated control animals (n=2). Echocardiography detected PH changes by day 4 and severe PH over 14 days of continued hypoxic exposure. RV dysfunction at day 4 was less severe in vorinostat-treated compared to untreated hypoxic calves. Cardioprotective effects were partially maintained following cessation of treatment through the duration of hypoxic exposure, accompanied by hemodynamic evidence suggestive of reduced pulmonary vascular stiffening, and modulated expression of HDAC1 protein and genes involved in RV and pulmonary vascular remodeling and pathological RV hypertrophy. Control calves did not develop PH, nor show adverse cardiac or clinical effects. These results provide novel translation of epigenetic-directed therapy to a large animal severe PH model that recapitulates important features of human disease.